2009
DOI: 10.1111/j.1439-0469.1990.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal characterization of three species of the genus Mastomys in Senegal

Abstract: Mastomys rats are present as three distinct karyomorphs in Senegal. Specific assignations were accorded to each form on the basis of chromosomal, reproductive and distribution characteristics. Mastomys erythroleucus (2n = 38, NFa = 52) is ecologically a generalist, M. huberti (2n = 32, NFa = 44) is restricted to humid biotopes and M. cfnatalensrs (2n = 32, NFa = 54) is strictly commensal and found in Southeastern Senegal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
(10 reference statements)
2
20
0
Order By: Relevance
“…The same diploid number and NFa varying from 44 to 46, due to inversion polymorphism involving pair 10, was described repeatedly in this species (Hubert et al 1983;Duplantier et al 1990;Britton Davidian et al 1995;Volobouev et al 2002b). In our sample one of the females was heterozygous for this rearrangement ( Figure 2).…”
Section: Species Assignation and Taxonomic Assessmentmentioning
confidence: 93%
See 1 more Smart Citation
“…The same diploid number and NFa varying from 44 to 46, due to inversion polymorphism involving pair 10, was described repeatedly in this species (Hubert et al 1983;Duplantier et al 1990;Britton Davidian et al 1995;Volobouev et al 2002b). In our sample one of the females was heterozygous for this rearrangement ( Figure 2).…”
Section: Species Assignation and Taxonomic Assessmentmentioning
confidence: 93%
“…In the Nimba region, Gautun et al (1986) described two morphs but failed to attribute them and no karyotypes were Figure 12. Correspondence analysis graph (F16F2) on presence-absence data of small rodent genera (after Table V Duplantier et al (1990Duplantier et al ( , 1997 in S. Senegal (Casamance, Kedougou), M. erythroleucus is sympatric with M. huberti and M. natalensis. In Senegal M. erythroleucus is found in all habitats, but M. huberti is restricted to humid zones and cultures while M. natalensis is found only in villages (Duplantier & Granjon 1988).…”
Section: Mastomys Species Distribution In West Guineamentioning
confidence: 99%
“…The genus Mastomys generates taxonomic confusion. The two species differ in chromosome number, some biochemical traits, and sperm morphology (Duplantier et al, 1990;Kneidinger, 2008). 7.28) and Mastomys coucha.…”
Section: Taxonomymentioning
confidence: 99%
“…Originally described as South African species, animals with identical chromosomal features have been found in Tanzania and Senegal in West Africa (Duplantier et al, 1990). Given the confusion with taxonomic status, it probably suffices to state that the multimammate rat is one of the most widely distributed and abundant rodents in Africa.…”
Section: Distributionmentioning
confidence: 99%
“…Since the late 1970s, however, the application of cytogenetic and electrophoretic methods for resolving taxonomic issues revealed that M. natalensis sensu lato was a species complex comprising at least 8 cryptic species that, although morphologically difficult to distinguish, differ in diploid chromosome number (2n) and fundamental number, hemoglobin electromorphs and allozyme properties, or both (Gordon 1978;Green et al 1980;Hallett 1977;Duplantier et al 1990). More recently, it has also been shown that 4 of these cryptic species also differ in mitochondrial cytochrome-b sequences (Lecompte et al 2005).…”
mentioning
confidence: 99%